Aqueous CO2 Reduction with High Efficiency Using α‐Co(OH)2‐Supported Atomic Ir Electrocatalysts. (27th February 2019) - Sun, Xiaofu; Chen, Chunjun; Liu, Shoujie; Hong, Song; Zhu, Qinggong; Qian, Qingli; Han, Buxing; Zhang, Jing; Zheng, Lirong
Abstract: Electrochemical reduction of CO2 into energy‐dense chemical feedstock and fuels provides an attractive pathway to sustainable energy storage and artificial carbon cycle. Herein, we report the first work to use atomic Ir electrocatalyst for CO2 reduction. By using α‐Co(OH)2 as the support, the faradaic efficiency of CO could reach 97.6 % with a turnover frequency (TOF) of 38290 h −1 in aqueous electrolyte, which is the highest TOF up to date. The electrochemical active area is 23.4‐times higher than Ir nanoparticles (2 nm), which is highly conductive and favors electron transfer from CO2 to its radical anion (CO2 .− ). Moreover, the more efficient stabilization of CO2 .− intermediate and easy charge transfer makes the atomic Ir electrocatalyst facilitate CO production. Hence, α‐Co(OH)2 ‐supported atomic Ir electrocatalysts show enhanced CO2 activity and stability. Abstract : Atomares Ir auf α‐Co(OH)2 in hoher Dichte zeigt eine herausragende Leistung in der Reduktion von CO2 zu CO. Die Faraday‐Effizienz kann 97.6 % bei einem TOF‐Wert von 38 290 h −1 erreichen. Der hohen katalytischen Aktivität liegen eine große Anzahl aktiver Zentren für die Adsorption und Aktivierung von CO2 sowie eine gute Effizienz in der Stabilisierung des CO2 .− ‐Intermediats zugrunde.